Contemporary Trends in the Surgical Management of Nasal Septal Perforations: A Community Survey - Delaney, Sean William; Kridel, Russell W.H. (Facial Plastic Surgery, 2019)
There currently exists an overabundance of publications advocating different septal perforation repair methods. The objective of this article was to examine the preponderance of techniques and trends in the surgical management of septal perforations in the practices of otolaryngologists, rhinologists, and facial plastic surgeons. The study was designed as a multicenter cross-sectional survey. The participants were members of the American Academy of Facial Plastic and Reconstructive Surgery and the American Rhinologic Society. Septal perforation closure rates and perforation repair approach, technique, and interposition graft material preferences were the main outcomes. A total of 320 respondents completed the survey, of whom 75% performed perforation repairs. The success rates in closing perforations < 1 cm, 1–2 cm, and > 2 cm were 84%, 64%, and 31%, respectively. The respondents had a similar preference for the endoscopic (52%) and external rhinoplasty (49%) approaches, followed by the endonasal approach (43%). Bilateral intranasal mucosal advancement flaps (79%) and unilateral intranasal mucosal rotational or advancement flaps (60%) were the favored repair techniques. Most respondents (84%) incorporated an interposition graft and intranasal splints (89%) for the repair, and the most popular interposition graft material was acellular dermis (63%). The self-reported perforation closure success rates in this survey were lower than those published in the literature, a phenomenon possibly explained by the premise that surgeons with favorable outcomes are more apt to share their results. The preferred surgical approach was evenly distributed between the external rhinoplasty and endoscopic approaches and influenced by a surgeon's training, perforation size and location, and the need for concomitant rhinoplasty. This study is the first to characterize contemporary community trends in the surgical closure of septal perforations and demonstrates that while preference for perforation repair approach among the respondents varied, surgeons favored septal perforation repair using bilateral intranasal mucosal advancement flaps with an interposition graft.
Keywords: rhinoplasty; septoplasty; nasal reconstruction; nasal physiology